2003
DOI: 10.3171/spi.2003.99.3.0257
|View full text |Cite
|
Sign up to set email alerts
|

Improved accuracy of computer-assisted cervical pedicle screw insertion

Abstract: Object. The authors introduce a unique computer-assisted cervical pedicle screw (CPS) insertion technique used in conjunction with specially modified original pedicle screw insertion instruments. The accuracy of screw placement as well as surgery-related outcome and complication rates were compared between two groups of patients: those in whom a computer-assisted and those in whom a conventional manual insertion technique was used. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 23 publications
3
148
0
6
Order By: Relevance
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [12,13,19,24,26,30] reported follow-up period ranging from 15 to 34 months, while one study followed the patients to clinical and radiological bony fusion [16], but none reported on rate of fusion achieved.…”
Section: Fusion Ratementioning
confidence: 99%
“…A decrease in perforation rates from 66.5 to 10.6% was shown. Three other studies have also found a benefit in using computer guidance during such surgery [13,19,31]; however, no matter which technique is employed, there is still a need for the surgeon to understand the anatomical landmarks, We, along with the paper by Hacker et al [10], advocate the use of the posterior elements as a reference for the trajectory of pedicle screw insertion. However, there is a significant limitation to both our techniques, which they also mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Developments in computer-assisted surgery have subsequently been analysed and have shown a higher success rate than other image-guided techniques [19,24]. However, as Kamimura et al [13] quite rightly pointed out, the surgeon still needs to know the pedicle morphology to ensure that the computer guides the screws correctly.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique has a potential risk of nerve root, spinal cord and vertebral artery injury due to a small corridor of safe screw placement [31,39,41], recent clinical studies demonstrate that relevant complications do not occur frequently [2,9,11,15,18,24,26,29,47,48]. The axis of the cervical pedicles to the sagittal midline plane vary between 25 and 60°and makes a wide exposure of the spine necessary [14].…”
Section: Introductionmentioning
confidence: 99%